EVALUASI STUDI PENEMPATAN TRANSFORMATOR DAN JATUH TEGANGAN PADA PENYULANG PALOLO MENGGUNAKAN SURVEI PEMETAAN SOFTWARE ODK (OPEN DATA KIT) COLLECT - Mohamad Risky; Maryantho Masarrang; Sari Dewi (Foristek, 2020)
Power of energy generated from station is the some all the phase. The use of electricity as well as efforts to satisfy customers or consumers of electricity by optimizing the distribution network. By evaluating the distribution network of PT. PLN with the ODK (Open Data Kit) collect method will make it easier to take field samples, find out the long distance of the transformer point by making an arcgis simulation distribution map. After all the data is obtained then to find the voltage drop can be done by analyzing the length of the stretch, the power of the transformer so that it will be known what percentage of voltage drop in the location farthest from the power center.